The Role of Islamic Education in Teaching Moral Values to Students - Nur Zaytun Hasanah; Shafira Dhaisani Sutra; Istiqomah Istiqomah; M Hajar Dewantara; Saad Boulahnane (Program Studi PGMI UIN Salatiga, 2022)
The purpose of this study is to interpret the consequential role of Islamic education in shaping students’ noble character. Islam, which was supposed to be the basis for the mindset and attitude pattern in a Muslim-majority country, is no longer a solid reference. What has long been regarded as foul, non-Islamic behaviors are increasingly rampant today. Public display of blatant nudity and sex related activity shown on social media has become a disconcerting phenomenon. This research is a type of qualitative research with a qualitative descriptive research approach. The data collection techniques adopted observation, documentation, and interviews to determine the role of Islamic education in shaping students' morals. Based on the data obtained, students at SD Khoiru Ummah Yogyakarta learning Islamic education are taught about Aqidah, sharia, and morals. The results show that the role of teaching and learning Islamic education can shape the character of students who have noble character where this is reflected in their thinking, their fidelity to religion, their courage to voice the truth, and their good influence on their families, communities, and society.